Effects of a 12-hour shift system on sleep and cardiovascular health of male machine and plant operators – a longitudinal study over four years - Seibt, Reingard; Kreuzfeld, Steffi; Hunger, Bettina (Frontiers in Public Health, 2025)
BackgroundData on the risks and effects of shift systems involving night work are inconsistent. In particular, there is a lack of longitudinal studies on the impact of 12-h shift systems on indicators of sleep, cardiovascular health and work-life balance. Therefore, this study compared machine and plant operators (MPO) who worked in a rotating 12-h shift system or only during the day, both at baseline (T1) and at follow-up 4 years later (T5).MethodsData were collected annually and included a questionnaire on shift work and sleep as well as a cardiovascular screening programme. The sample for analysis consisted of 45 shift (SW) and 30 day workers (DW) (mean age T1: 40 years). Sleep behaviour was examined by sleep quality and quantity (PSQI score), cardiovascular health by blood pressure, body mass index (BMI), blood lipids, glycosylated haemoglobin (HbA1c) and PROCAM score. Work-life balance was assessed on the basis of life satisfaction and impairments. Analyses of covariance with repeated measures were used to determine longitudinal changes in the indicators between T1 and T5.ResultsAt T1, SW showed significantly poorer sleep quality (d = 0.58) and shorter sleep duration (M = 366 min vs. 438 min, d = 1.38) compared to DW. These effects increased significantly in SW only after night shifts at T5 (M = 5.1 pts, η2p = 0.13, sleep duration: M = 318 min). At T1, SW differed from DW only by a significantly higher blood pressure (d = 0.60/0.49), BMI (d = 0.68) and PROCAM score in trend (p = 0.122). Lipids and HbA1c were comparable between the two groups. The means of the PROCAM score were in the low-moderate range, predicting a risk of heart attack <10% for 87% of the MPOs. At T5, the group differences for cardiovascular health from T1 were confirmed. SW achieved significantly higher satisfaction at T5 (η2p = 0.22); it corresponded to that of DW. Both groups reported significantly fewer impairments at T5 (d = 0.68/0.58).ConclusionAt T5, the 12-h shift system demonstrably changed sleep behaviour but not cardiovascular health. Sleep deficits could not be compensated. The 12-h shift system seems to offer advantages for work-life balance.